2019
DOI: 10.3390/ma12213539
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and Post-Buckling Behavior of Uniform and Variable-Density Lattice Columns Fabricated Using Additive Manufacturing

Abstract: Lattice structures are known for their high strength-to-weight ratio, multiple functionalities, lightweight, stiffness, and energy absorption capabilities and potential applications in aerospace, automobile, and biomedical industry. To reveal the buckling (global and local) and post-buckling behavior of different lattice morphologies, both experimental and simulation-based studies were carried out. Additionally, a variable-density lattice structure was designed and analyzed to achieve the optimal value of crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In the manufacturing industry, high-speed 3D printing technologies are explored in recent time such as high-aspect-ratio nozzles for micro-extrusion [89]; integration of powder bed technology, multi-jet function technology, and high-speed sintering technology [90], to name a few. Moreover, as described in [91], special structural element such as lattice column and beam, or cellular structure which are suitable to construct using 3D printing, can be explored for the construction projects.…”
Section: Prospect Of 3dcpmentioning
confidence: 99%
“…In the manufacturing industry, high-speed 3D printing technologies are explored in recent time such as high-aspect-ratio nozzles for micro-extrusion [89]; integration of powder bed technology, multi-jet function technology, and high-speed sintering technology [90], to name a few. Moreover, as described in [91], special structural element such as lattice column and beam, or cellular structure which are suitable to construct using 3D printing, can be explored for the construction projects.…”
Section: Prospect Of 3dcpmentioning
confidence: 99%
“…A wide range of studies were conducted to buckle beams, planes, and shells [ 32 , 33 , 34 ]. However, to investigate critical buckling of lattice structures, Nazir et al [ 35 ] studied the variable-density lattice structure columns for critical and post-buckling behavior. They revealed that critical buckling depends on several parameters, such as the thickness of the beam, orientation, second moment of inertia, and mass distribution in the structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, countable researchers have investigated surface-based lattice structures. Similarly, the lattice structure column was studied with limited numbers, whereas holes/pores and elliptical shape-based columns were studied extensively [ 33 , 34 , 35 ]. Considering these research gaps, a novel lattice design named O-Surface (OS) was introduced and compared with the existing Sea Urchin structure (SU) to investigate and reveal its inherent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fused deposition modeling (FDM) is a 3D printing process that uses a continuously extruded filament through a heated printer core. This is universally accomplished with thermoplastic materials that have varying mechanical and physical properties that can be tailored to the function of the desired print [2]. FDM 3D printing has been investigated for creating lumbar vertebral models for education and procedural simulation [3,4].…”
Section: Introductionmentioning
confidence: 99%